2011
DOI: 10.1038/nrn2994
|View full text |Cite
|
Sign up to set email alerts
|

The integration of negative affect, pain and cognitive control in the cingulate cortex

Abstract: PrefaceIt has been argued that emotion, pain, and cognitive control are functionally segregated in distinct subdivisions of the cingulate cortex. But recent observations encourage a fundamentally different view. Imaging studies indicate that negative affect, pain, and cognitive control activate an overlapping region of dorsal cingulate, the anterior midcingulate cortex (aMCC). Anatomical studies reveal that aMCC constitutes a hub where information about reinforcers can be linked to motor centers responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

113
1,576
6
16

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,792 publications
(1,711 citation statements)
references
References 216 publications
(259 reference statements)
113
1,576
6
16
Order By: Relevance
“…Consistent with our hypothesis, this increased neural activation occurred within the dACC. Activation in the dACC is noteworthy because the dACC is implicated in cognitive-emotional control, is activated in response to challenging tasks and negative emotional situations, and determines the degree of control recruited (Gasquoine, 2013;Shenhav et al, 2013;Shackman et al, 2011). We also conceptually replicated prior research showing heightened amygdala activation to negative emotional stimuli in people with the MAOA-L genotype.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Consistent with our hypothesis, this increased neural activation occurred within the dACC. Activation in the dACC is noteworthy because the dACC is implicated in cognitive-emotional control, is activated in response to challenging tasks and negative emotional situations, and determines the degree of control recruited (Gasquoine, 2013;Shenhav et al, 2013;Shackman et al, 2011). We also conceptually replicated prior research showing heightened amygdala activation to negative emotional stimuli in people with the MAOA-L genotype.…”
Section: Discussionsupporting
confidence: 74%
“…The dACC is well connected with the lateral prefrontal cortex, OFC, and insula (Shackman et al, 2011), all of which have been implicated in anger regulation (Fabiansson, Denson, Grisham, Moulds, & Schira, 2012). Moreover, the dACC is activated when people are provoked to anger, and this activation is strongest for people high in trait aggression (Denson, Pedersen, Ronquillo, & Nandy, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation within the PCC was suggested to signal the subjective preferences that guide visual orienting within a gambling task comprising risky choices (McCoy and Platt, 2005). ACC and PCC were reported to be involved throughout all phases of risky decision making in a task concerning financial aspects (Engelmann and Tamir, 2009;Shackman et al, 2011).…”
Section: Anatomical and Functional Features Of The Brain Regions Invomentioning
confidence: 99%
“…Finally, the AI and dACC were found to be commonly involved in conflict process [Botvinick et al, 1999;Fan et al, 2008], cognitive control [Chein and Schneider, 2005;Egner, 2009], and salience detection [Menon and Uddin, 2010;Seeley et al, 2007]. A previous meta-analysis indicated that the ACC might be the region where pain, negative affect and cognitive control are integrated [Shackman et al, 2011]. Likewise, the AI has also been identified in a variety of tasks associated with cognition, emotion or the interaction between them [Gu et al, 2012[Gu et al, , 2013aFan et al, 2011].…”
mentioning
confidence: 99%